Pengaruh Frekuensi Miksi Terhadap Insomnia Pada Ibu Hamil Trimester III di Klinik Yapida Gunung Putri Tahun 2022 - Inne Bunga Heliana; Elfira Sri Futriani (Wellness And Healthy Magazine, 2022)
Increasing frequency of myction in pregnant women is a thing that often occurs when pregnant women enter the third trimester and the gestational age increases, the more complaints felt by pregnant women. Disruption of comfort during pregnancy can have an impact on pregnant women, namely the quality of sleep that results in insomnia. Objective to Knowing the effectiveness of frequency on insomnia in pregnant women in the third trimester of pregnancy at the Yapida Gunung Putri Clinic for the period 2022. The method in this study uses quantitative descriptive with a cross-sectional sample approach using a total sampling of 50 third trimester pregnant women, the instrument used is data retrieval by means of closed questionnaires given to pregnant women in the third trimester, bivariate analysis using the chi square test. Of the 50 respondents, TM III, the frequency of Miksi was less than 4 times as many as 11 people. 6 people had mild insomnia (54.55%), who had moderate insomnia (27.27%) and 2 people had severe insomnia (18.18%). Pregnant women TM III who have a frequency of 4-8 times as many as 36 people. Of the 36 people, who had mild insomnia as many as 1 person (2.78%), who had moderate insomnia as many as 19 people (52.78%) and who had severe insomnia as many as 16 people (44.44%). Pregnant women TM III who have a frequency of miction more than 8 times as many as 3 people. Of the 3 people, none had mild insomnia, who had moderate insomnia as much as 1 person (33.33%) and who had severe insomnia as many as 2 people (66.67%). Chi Square results show that there is an influence of myx frequency on insomnia in pregnant women trimester III (p-value 0.001). It is expected for pregnant women to better control the frequency of myction at night, so that insomnia does not occur and maintain sleep quality. Abstrack: Bertambahnya Frekuensi miksi pada ibu hamil merupakan hal yang sering terjadi ketika ibu hamil memasuki trimester III dan usia kehamilan semakin bertambah, semakin banyak keluhan yang dirasakan oleh ibu hamil. Gangguan kenyamanan selama kehamilan dapat memberi dampak pada ibu hamil yaitu kualitas tidur yang mengakibatkan insomnia. Tujuan Penelitian untuk mengetahui pengaruh frekuensi miksi terhadap insomnia pada ibu hamil trimester III di Klinik Yapida Gunung Putri periode tahun 2022. Metode pada penelitian ini menggunakan descriptive kuantitatif dengan pendekatan cross-sectional sampel menggunakan total sampling sebanyak 50 ibu hamil Trimester III, Instrument yang digunakan adalah pengambilan data dengan cara kuisioner tertutup yang di berikan kepada ibu hamil trimester III, analisis bivariat menggunakan Uji chi square. Dari 50 responden ibu hami TM III frekuensi Miksi kurang dari 4 kali sebanyak 11 orang. yang memiliki insomnia ringan sebanyak 6 orang (54,55%), yang memiliki insomnia sedang sebanyak 3 orang (27,27%) dan yang memiliki insomnia berat sebanyak 2 orang (18,18%). Ibu hamil TM III yang memiliki frekuensi Miksi 4 – 8 kali sebanyak 36 orang. Dari 36 orang tersebut, yang memiliki insomnia ringan sebanyak  1 orang (2,78 %), yang memiliki insomnia sedang sebanyak 19 orang (52,78%) dan yang memiliki insomnia berat sebanyak 16 orang (44,44%). Ibu hamil TM III yang memiliki frekuensi Miksi lebih dari 8 kali sebanyak 3 orang. Dari 3 orang tersebut, tidak ada yang memiliki insomnia ringan, yang memiliki insomnia sedang sebanyak 1 orang (33,33%) dan yang memiliki insomnia berat sebanyak 2 orang (66,67%). Hasil Chi Square menunjukkan bahwa ada pengaruh frekuensi miksi terhadap insomnia pada ibu hamil Trimester III (p-value 0,001). Diharapkan untuk ibu hamil lebih mengontrol frekuensi miksi pada malam hari, sehingga tidak terjadi insomnia dan menjaga kualitas tidur.